The Role of Forensic Accounting in Preventing Fraud and Corruption in the Public and Private Sectors - Indrajaya Tuharea, Firdaus; Hasyim Ashari, Muhammad; Agusti, Anatia; Andika Rifdayanti, Amirah (Dhana, 2024)
This study aims to examine the role of forensic accounting in preventing fraud and corruption in the public and private sectors. Forensic accounting, which combines accounting knowledge with investigative techniques, serves as a tool to detect and prevent fraud and manipulation that can harm an organization. This study uses a Systematic Literature Review (SLR) approach to identify, evaluate, and analyze relevant literature related to the role of forensic accounting in preventing fraud and corruption. The results of the study indicate that the application of appropriate forensic accounting techniques can strengthen internal controls, increase transparency, and detect early signs of fraud before it causes significant losses. In the public sector, forensic accounting plays a role in ensuring accountable and transparent management of public funds, and helps detect and prevent corruption in government procurement processes and projects. In the private sector, the application of techniques such as data analysis, document examination, and forensic audits can identify suspicious transactions and maintain the integrity of a company's financial statements. In addition, human resource training on business ethics and the importance of transparency plays an important role in building an organizational culture that supports effective oversight. Based on these findings, this study recommends that organizations in both sectors focus more on strengthening internal control systems, as well as providing forensic accounting training to auditors and financial managers. Implementing better prevention strategies can create a cleaner, more transparent and accountable environment, which ultimately strengthens the organization's reputation and reduces the risk of fraud and corruption.